Availability, pricing and affordability of essential medicines in Eastern Ethiopia: a comprehensive analysis using WHO/HAI methodology - Mekonnen Sisay; Firehiwot Amare; Bisrat Hagos; Dumessa Edessa (Taylor & Francis Group, 2021)
Background Access to essential medicines is a universal human right and availability and affordability are the preconditions for it. In line with the sustainable development goals, World Health Organization (WHO) has outlined a framework that assists the policy makers to improve access to essential medicines for universal health coverage by 2030. However, the availability and affordability of essential medicines remains suboptimal in several low-income countries. Therefore, this study was designed to investigate the availability, pricing and affordability of essential medicines in eastern Ethiopia. Methods A cross-sectional study design was employed to conduct this study. Public and private health facilities found in Eastern Ethiopia and which fulfilled criteria set forth by WHO/Health Action International (HAI) guideline and essential medicines listed on WHO/HAI guideline and essential medicine list of Ethiopia were included. Accordingly, 60 medicine outlets were selected based on the WHO/HAI standardized sampling methodology. A standardized data collection tools developed by WHO/HAI, with necessary modifications, was employed to collect the data. Median Price Ratio (MPR) was computed as a ratio of median local buyers' price to international buyers' reference price. The Mann-Whitney U test was employed to compare the median buyers' price between public and private health facilities. Kruskal-Wallis test was also run to explore the median price difference among all facilities. Treatment affordability was calculated based on the number of days of wage of the lowest-paid government employee of Ethiopia required to purchase the prescribed regimen. Results The overall percent availability of originator brand (OB) versions of essential medicines was found to be 3.6% (range: 0.0-31.7%), with the public and private sectors contributing 1.43% and 5.50%, respectively. The overall percent availability of lowest price generics (LPGs) was 46.97% (range: 1.7-93.3%) (Public: 42.5%; private: 50.8%). Only eight LPGs (16.0%) met the WHO target of 80%. The Mann-Whitney U test indicated that 64% drugs showed statistically significant median price difference between public and private settings (p < 0.05). The MPR value indicated that the median buyers' price of drugs in private sector were more than four times the international reference price in 30% of drugs. The percentage of unaffordable medicine were 72.09 and 91.84% for public and private facilities, respectively, with 79.17% of the medicines were unaffordable when both settings were combined. Conclusion Only 16% of the surveyed medicines surpassed the WHO cut-off point of 80%. Nearly one-third of drugs in the private sector had a price of more than four times compared to the international reference prices. Moreover, four out of five drugs were found unaffordable when both settings were combined, demanded several days of wage of lowest paid government employee. This finding calls a prompt action from stakeholders to devise a strategy that help promote the access of essential medicines and rescue the struggling healthcare system of Ethiopia.